Conceptual metaphor in meditation discourse: an analysis of the spiritual perspective - Silvestre-López, Antonio-José (Penerbit Universiti Kebangsaan Malaysia, 2020)
Meditation has spread beyond the frontiers of religion to go global in other areas of social practice, including secular and spiritual-but-not-religious contexts. Conceptual metaphor, as proposed by Lakoff (1993) has been described as a powerful mechanism to facilitate the communication of first-person experiences connected to religious and lay contemplative practice, including meditation and enlightenment, as reported in several studies. Despite the detachment of the spiritual-but-not-religious movement from other areas of practice, the question of how metaphor is used in discourse about meditation within this perspective has not been addressed. This paper investigates the role of conceptual metaphor in spiritual-but-not-religious meditation discourse through a bottom-up qualitative analysis of a corpus of talks about meditation given by three highly-recognized spiritual teachers. Results chart the topics that are addressed more frequently through metaphor in the corpus (metaphor target domains), describe the range of areas of experience (source domains) used to characterise metaphorically the three most frequent target domains (THOUGHT, THE PRESENT MOMENT, MEDITATOR), and discuss fundamental differences in non-deliberate and deliberate conceptual metaphor use with the help of a selection of examples from the corpus. The findings provide evidence of relevant metaphors used to model the experience and practice of meditation in spiritual-but-not-religious settings and how they are rendered in discourse. Comparisons with metaphorical models already identified in religious and secular discourse contexts are also established, with a special focus on the models that have been transferred from traditional religious meditation spheres to current contexts of social practice.